Antecedents of Employee Loyalty in Educational Setting: An Empirical Study - O. Sihombing, Sabrina; P. Berlianto, Margaretha (Universitas Prasetiya Mulya, 2017)
No studies have been conducted to link three variables of work values, internal marketing, and job satisfaction in predicting employee loyalty. Therefore, this research aims to fulfill the gap by developing a model that include work values, internal marketing, and job satisfaction in assessing employee loyalty in educational context. This research apply a judgmental sampling with the sample size of 200 lecturers from a private universities in Tangerang. Structural equation modeling was applied in testing the research hypotheses. The results showed that there is one out of three hypotheses that was not supported. That hypothesis is the relationship between internal marketing and job satisfaction.